Reflecting on Imbalance Data Issue when Teaching Performance Measures - Škrabánek, Pavel; Majerík, Filip (Springer, 2017)
Importance of soft computing methods has continuously grown for many years. Particularly machine learning methods have been paid considerable attention in the business sphere and subsequently within the general public in the last decade. Machine learning and its implementation is the object of interest of many commercial subjects, whether they are small companies or large corporations. Consequently, well-educated experts in the area of machine learning are highly sought after on the job market. Most of the technical universities around the world have incorporated the machine learning into their curricula. However, machine learning is a dynamically evolving area and the curricula should be continuously updated. This paper is intended to support this process. Namely, an imbalance data issue, in context of performance measures for binary classification, is opened, and a teaching method covering this problem is presented. The method has been primary designed for undergraduate and graduate students of technical fields; however, it can be easily adopted in curricula of other fields of study, e.g. medicine, economics, or social sciences.
Zohlednění problematiky nevyváženosti datové sady při výuce metod určených k evaluaci binárních klasifikátorů
Keywords: machine learning, binary classification, imbalanced data, performance measures, teaching method; strojové učení, binární klasifikátor, nevyvážená datová sada, metriky pro měření výkonu, výuková metoda